2000
DOI: 10.1046/j.1460-9568.2000.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine‐independent action of cocaine on striatal and accumbal neurons

Abstract: Increasing evidence suggests that dopamine (DA) mechanisms alone cannot fully explain the psychoemotional and behavioural effects of cocaine, including its ability to induce drug-taking behaviour. Although it is known that cocaine, after intravenous administration or smoking, may reach brain levels high enough to inhibit Na+ transport, the role of this action remains unclear. To examine the contribution of local anaesthetic and DA mechanisms to changes in striatal and accumbal neuronal activity induced by coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…In a recent in vivo study, cocaine was found to exert a preferential local-anaesthetic-like action on striatal neurons (Kiyatkin and Rebec 2000), suggesting that this kind of effect might in principle have occurred in our experimental condition. The quiescent behavior of spiny neurons in vitro, however, prevented the observation of cocaine effects on voltage dependent-sodium channels.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In a recent in vivo study, cocaine was found to exert a preferential local-anaesthetic-like action on striatal neurons (Kiyatkin and Rebec 2000), suggesting that this kind of effect might in principle have occurred in our experimental condition. The quiescent behavior of spiny neurons in vitro, however, prevented the observation of cocaine effects on voltage dependent-sodium channels.…”
Section: Discussionmentioning
confidence: 68%
“…26, NO. 2 cently reported that cocaine modulates striatal neuron firing activity independently of a DA-mediated mechanism (Kiyatkin and Rebec 2000). To test whether the inhibitory effect of both cocaine and amphetamine on striatal GABAergic transmission was caused by the action of these drugs on DAergic nerve terminals of the striatum, we recorded striatal neurons from rats with 6-OHDA-induced lesion of the homolateral substantia nigra.…”
Section: Effects Of Da Denervation and Of Pharmacological Blockade Ofmentioning
confidence: 99%
See 3 more Smart Citations